Increased Emotional Spiritual Quotient through Reflective Learning in Clinical Nursing Students at Syarif Hidayatullah State Islamic University - Setiowati, Dwi; Utomo, Waras Budi (Universitas Pendidikan Indonesia, 2021)
ABSTRAKIntroduction: Reflection is carried out in the realm of practice, the role of professionals, such as teaching and education. Reflection is also used in the health sector, especially nursing practice. Reflection is important in clinical learning for professional and students' intellectual development. The nursing program on nurses learning with the Competency-Based Curriculum at Syarif Hidayatullah State Islamic University, Jakarta has only begun from 12th generation which is still running in hospitals with scientific and Islamic integration. Aims: the purpose and significance of this research is to determine the effect of Reflection on ESQ clinical nursing students of Syarif Hidayatullah State Islamic University, Jakarta. Method: the research method used was a pre-experimental design. Respondents were 36 nursing students, with purposive sampling. Interventions used Gibbs’s reflective learning step and ESQ questionnaire The analysis data used t dependent test. Results: the results showed that there were significant differences in the ESQ of Nurse students before and after they were given reflective learning. Discussion: self-reflection learning as part of clinical nurse learning is able to develop student ESQ and is in line with the integration of science and Islam at UIN Syarif Hidayatullah. It is needed the sustainable development and monitoring of learning with reflective learning in nurses study programs for nurses students so that ESQ as a student soft skill can be optimally achieved to improve the quality of nurses' education in Syarif Hidayatullah State Islamic University, Jakarta.ABSTRAKPendahuluan: refleksi dilakukan pada ranah praktik, peran peran professional seperti bidang pengajaran dan pendidikan. Refleksi juga digunakan pada bidang kesehatan terutama praktik keperawatan. Refleksi merupakan hal yang penting dalam pembelajaran klinik untuk pengembangan professional dan intelektual mahasiswa. Program studi ilmu keperawatan dengan kurikulum berbasis kompetensi di UIN Syarif Hidayatullah Jakarta baru dimulai pada angkatan 12 dan pembekajaran Ners yang masih berjalan di rumah sakit dengan integrasi keilmuan dan keislaman. Tujuan: tujuan dan signifikansi penelitian ini adalah mengetahui pengaruh refleksi terhadap ESQ mahasiswa ners psik Syarif Hidayatullah Jakarta. Metode: Metode penelitian yang digunakan menggunakan desain pra eksperimen dengan 36 sampel, purposive sampling, dan uji t dependent. Hasil: Hasil penelitian didapatkan terdapat perbedaan signifikan ESQ mahasiswa program Ners sebelum dan sesudah diberikan perlakuan reflektive learning. Pembahasan: Perlunya pengembangan dan monitoring berkelanjutan pembelajaran dengan reflektive learning pada program studi Ners pada mahasiswa Ners sehingga ESQ sebagai softskill mahasiswa dapat optimal dicapai dalam upaya peningkatan mutu pendidikan Ners UIN Syarif Hidayatullah Jakarta.